Efficient Resource Allocation and Utilization: The Missing Link in Nigeria’s Quest for Sustainable Development - Ehiorobo Abraham Osa (Economics and Business)
This study examines resource allocation and utilization in Nigeria as the missing link in the nation’s quest for sustainable development. The main objective of the research is to examine how inefficient allocation and utilization of material, human and financial resources has made the attainment of sustainable development goals (SDGs) elusive in Nigeria. Given the abundant resources at the disposal of successive regimes in the country, it is difficult to explain why the citizens remain desperately poor with 70 percent living below poverty line. The excruciating poverty faced by the rural majority and the urban poor has led some people into indulging in unwholesome practices such as armed robbery, pipeline vandalism, prostitution, risky migrations, advanced fee fraud and other forms of social vices. The paper utilizes a qualitative design based on the interpretivist philosophy while the ontological orientation is subjectivism. Findings from the study indicate that there has been gross inefficiency in resource allocation and utilization in Nigeria due to corruption, ethnic prejudices, bad governance practices, absence of accountability, lack of transparency and wasteful spending on frivolous activities. Conclusion drawn from the study indicates that if proper project planning, execution, monitoring and evaluation are carried out in a transparent manner, and resources are efficiently allocated and utilized, Nigeria would be on the path to sustainable development. The paper therefore recommends that economic and technical efficiencies should be embraced in resource allocation and utilization for Nigeria to attain sustainable development goals.